Time trends of major cancers incidence and mortality in Guangzhou, China 2004–2015: A Joinpoint and Age–Period–Cohort Analysis. (16th March 2021) - Luo, Ao; Dong, Hang; Lin, Xiao; Liao, Yu; Liang, Binglun; Chen, Long; Lin, Guozhen; Hao, Yuantao
Abstract: Background: Cancer is an important focus of public health worldwide. This study aims to provide a comprehensive overview of temporal trends in incidence and mortality of leading cancer in Guangzhou, China from 2004 to 2015. Methods: Data were collected from the population‐based registry in Guangzhou. Age‐standardized incidence rate (ASIR) and age‐standardized mortality rate (ASMR) were calculated and Joinpoint regression was used for evaluating the average annual percent changes (AAPC) among the entire study period and the estimated annual percent changes (EAPC) in time segments. The effects of age, period, and birth cohort were assessed by the age–period–cohort model. Results: The age‐standardized incidence and mortality by the world standard population decreased significantly among males with AAPC of −1.7% (95% CI: −3.0%, 0.2%) and −2.7% (95% CI: −4.3%, −1.1%) for all malignancies during 2004–2015, while among females, the age‐standardized incidence had a non‐significant reduction with AAPC of −1.3% (95% CI: −2.8%, 0.2%) and the age‐standardized mortality demonstrated a remarkable decline (AAPC −2.0%, 95% CI: −3.6%, −0.3%). For males, the most commonly diagnosed cancers were trachea, bronchus, and lung (TBL), liver, colorectal, nasopharyngeal, stomach, and prostate cancer. For females, breast, TBL, colorectal, liver stomach, and thyroid cancer ranked the top. Unfavorable trends were observed in ASIR of colorectal, thyroid, and prostate cancer. APC models yielded different ages, periods, and birth cohort effect patterns by cancer sites. Conclusions: Cancer burden remained a public health challenge in Guangzhou as the aging population and lifestyles changes, despite declines in incidence and mortality rates in some cancers. Surveillance of cancer trends contributed to valuable insights into cancer prevention and control. Abstract : We aimed to evaluate the temporal trends of incidence and mortality rates in leading cancers by sex over the decade in Guangzhou, with an emphasis to analyze the detached effect of age, period of diagnosis, and birth cohort. And the study provided insight into the major cancer types with a comprehensive perspective in cancer variation trends and highlight the priorities that deserve attention for targeted intervention.